An insight into the role of the N-terminal domain of Salmonella CobB in oligomerization and Zn2+ mediated inhibition of the deacetylase activity - Beura, Shibangini; Pritam, Pulak; Dhal, Ajit Kumar; Jana, Arindam; Dash, Aiswarya; Mohanty, Pritisundar; Panda, Alok Kumar; Modak, Rahul (Frontiers in Molecular Biosciences, 2024)
Prokaryotic deacetylases are classified into Nicotinamide adenine dinucleotide (NAD + ) dependent sirtuins and Zn 2+ dependent deacetylases. Nicotinamide adenine dinucleotide (NAD + ) is a coenzyme for redox reactions, thus serving as an essential component for energy metabolism. The NAD + dependent deacetylase domain is quite conserved and well characterized across bacterial species like CobB in E. coli and Salmonella, Rv1151c in Mycobacterium, SirtN in Bacillus subtilis etc. E. coli CobB is the only bacterial deacetylase with known crystal structure (PDB id: 1S5P), which has 91% sequence similarity with Salmonella CobB (SeCobB). Salmonella encodes 2 CobB isoforms-SeCobBS and SeCobBL, with a difference of 37 amino acids in its N-terminal domain (NTD). Hydrophobic nature of NTD leads to stable oligomerization of SeCobBL. Homology modelling based predicted structure of SeCobB showed presence a zinc binding motif of unknown function. Tryptophan fluorescence quenching induced by ZnCl2 showed Zn 2+ has weak interaction with SeCobBS but higher binding affinity towards SeCobBL, which clearly demonstrated crucial role of NTD in Zn 2+ binding. In presence of Zn 2+ , both isoforms had significantly reduced thermal stability and greater effect was observed on SeCobBL. Dynamic Light Scattering (DLS) studies reflected 9-fold increase in the scattering intensity of SeCobBL upon ZnCl2 addition in contrast to ~1 fold change in case of SeCobBS, indicating Zn 2+interaction lead to formation of large particles of SeCobBL. In vitro lysine deacetylase assay showed that SeCobB deacetylated mammalian histones, which can be inhibited in presence of 0.25-1.00 mM ZnCl2. Taken together our data conclusively showed that Zn 2+ strongly binds to SeCobBL through the NTD that drastically alters its stability, oligomeric status and enzymatic activity in vitro.Salmonella NAD + -dependent deacetylase (CobB), Zn 2+ -CobB interaction, CobB oligomerization, CobB homology modelling, Inhibition of CobB deacetylase activity, CobB thermal stability.